Mineral requirements for growth and maintenance of F1 Boer × Saanen male kids - Teixeira, I. A.M.A. [UNESP]; Härter, C. J. [UNESP]; Pereira Filho, J. M.; Da Silva Sobrinho, A. G. [UNESP]; Resende, K. T. [UNESP] (Oxford University Press (OUP), 2015)
The objective of this study was to determine the net requirements of minerals for the growth and maintenance of intact male F1 Boer × Saanen goat kids in the initial phase of growth. The following 2 experiments were performed: Exp. 1 was performed to determine the net growth requirements for Ca, P, Mg, Na, and K by F1 Boer × Saanen goat kids from 5 to 25 kg of BW and Exp. 2 was performed to determine the maintenance requirements of F1 Boer × Saanen goats from 15 to 25 kg BW. In Exp. 1, 32 intact male goat kids were distributed in a completely randomized design and mineral body composition was fit to an allometric equation in the form of a nonlinear model. To determine the mineral requirements for maintenance in Exp. 2, 21 intact male goat kids were distributed in a randomized block design, where the goat kids were subjected to 3 levels of feed restriction (0, 30, and 60% feed restriction). At the onset of Exp. 2, 7 goat kids were harvested and used to estimate the initial body composition (15 kg BW). Initial body composition was used to calculate the retention of minerals. The maintenance requirements were estimated by regressions obtained from the retention of minerals in the empty body and the intake of the mineral. The concentration of Ca, P, Na, and K in the empty BW decreased by 11, 13, 26, and 23% with the increase in BW from 5 to 25 kg (P < 0.01). As a consequence, our results showed that net requirements of Ca, P, Mg, Na, and K for weight gain decreased by 27.5, 27.8, 4.25, 43.2, and 39.7%, respectively, with the increase in BW from 5 to 25 kg (P < 0.01). The net requirements (g/kg of ADG) decreased from 9.7 to 7.0 for Ca, 6.5 to 4.7 for P, 0.38 to 0.36 for Mg, 0.88 to 0.50 for Na, and 1.9 to 1.2 for K when BW increased from 5 to 25 kg. The daily net requirements for maintenance per kilogram of BW were 38 mg of Ca, 42 mg of P, 1.6 mg of Mg, 5.0 mg of Na, and 19 mg of K. These results for the nutritional requirements of minerals may help to formulate more balanced diets for F1 Boer × Saanen goat kids in the initial growth phase.
Keywords: Body composition; Comparative slaughter; Crossbred goat; Magnesium; Potassium; Sodium